Detection of pseudorabies virus antibody in swine oral fluid using a serum whole-virus indirect ELISA. (July 2020) - Cheng, Ting-Yu; Buckley, Alexandra; Van Geelen, Albert; Lager, Kelly; Henao-Díaz, Alexandra; Poonsuk, Korakrit; Piñeyro, Pablo; Baum, David; Ji, Ju; Wang, Chong; Main, Rodger; Zimmerman, Jeffrey; et al.
We evaluated the detection of pseudorabies virus (PRV) antibodies in swine oral fluid. Oral fluid and serum samples were obtained from 40 pigs allocated to 4 treatment groups (10 pigs/group): negative control (NC); wild-type PRV inoculation (PRV 3CR Ossabaw; hereafter PRV); PRV vaccination (Ingelvac Aujeszky MLV; Boehringer Ingelheim; hereafter MLV); and PRV vaccination followed by PRV inoculation at 21 d post-vaccination (MLV-PRV). Using a serum PRV whole-virus indirect IgG ELISA (Idexx Laboratories) adapted to the oral fluid matrix, PRV antibody was detected in oral fluid samples from treatment groups PRV, MLV, and MLV-PRV in a pattern similar to serum. Vaccination alone produced a low oral fluid antibody response (groups MLV and MLV-PRV), but a strong anamnestic response was observed following challenge with wild-type virus (group PRV). Analyses of the oral fluid PRV indirect IgG ELISA results showed good binary diagnostic performance (area under ROC curve = 93%) and excellent assay repeatability (intra-class correlation coefficient = 99.3%). The demonstrable presence of PRV antibodies in swine oral fluids suggests the possible use of oral fluids in pseudorabies surveillance.